Variation in brownfield reuse of derelict agricultural premises in diverse rural spaces. (October 2021) - Navrátil, Josef; Krejčí, Tomáš; Martinát, Stanislav; Frazier, Ryan J.; Klusáček, Petr; Pícha, Kamil; Škrabal, Jaroslav; Osman, Robert
Abstract: Urban brownfield remediation and reclamation have attracted much attention, but rural spaces do not receive the same focus and suffer from the effects these sites have on society, the economy, and land. The objective of this study is to evaluate how social, economic, and environmental features affect agricultural brownfield regeneration between 2004 and 2018 through two case study regions in the southern Czech Republic. In 1221 muncipalties where a communist agricultural cooperative or a state farm operated in 1989, agricultural brownfields existed in 832 of the municipalities in 2004. A multinomial non-parametric regression method and CCA ordination revealed ties between agricultural brownfield reclamation and the characteristics of those municipalities. This shows a deep and before unknown consequence of agricultural brownfield regeneration. There was not a relationship between the size of an agricultural premise and its probability of being an agricultural brownfield. Larger agricultural brownfields are more likely to be (at least partially) regenerated. Lower agrcultural land costs drove the higher probability that a brownfield was reused between 2004 and 2018. Housing reuses more frequently occur in areas with low agricultural land costs. Similarly, agricultural reuses of those derelict premises is more likely in areas with a low price of agricultural land. However, larger municipalities did not experience a reclamation of their agricultural brownfields, and long-term brownfields may occur alongside any other type of reclaimed land. Highlights: The probability of an agricultural brownfield occurring is not correlated with premise size. Larger agricultural brownfields are more likely to be regenerated. Housing reuses are found in areas with low prices of agricultural land. Reusing an agricultural brownfield for agriculture again is more likely in areas with low land costs. Long-term brownfields can occur alongside any other type of reclaimed premises or land.